Interdisciplinarity in the training of Physical Culture Bachelor: Its history and trends/La interdisciplinariedad en la formación del Licenciado en Cultura Física: su historia y tendencias - Yolanda Valdés André; Jerry Bosque Jiménez; José Francisco Estradé Martínez; Daymara Guerra Bouza; Claudia Rodríguez Almeida (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2021)
The present society and its complex character, demands the training of increasingly competent and integral professionals capable of providing solutions to multiple and difficult social problems; this has required universities to review the difficulties and contradictions that are still present in this regard. In the field of physical activity and sport, the professional who works in the basic link in Cuba requires a solid interdisciplinary training, which the university as a training entity should promote, but has not always achieved, since it has not reached the desired levels in this aspect. To know how it has been in its historical development and to characterize the main tendencies of interdisciplinarity in the professional training of the Bachelor of Physical Culture, objective of this work, is of total importance to take pertinent actions and to direct such training with an interdisciplinary character. To achieve this, the results of completed research on the subject were analyzed from an analytical, interpretative or critical perspective of the authors, which allowed, as an opinion article or debate, to present the following text, in order to achieve an understanding of the developed topic.